(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Rasasastra is a branch of science deals with metals and minerals, Shilajathu (Bitumen) is one of the important herbo mineral drug in Rasasastra. It is also known as black bitumen or Asphaltum punjabinum, considered as mineral pitch. Shilajathu is widely used for treating number of diseases in various systems of medicine. It is an exudate of rocks having blackish brown colour, has been mentioned in Samhitas since ancient times. Shilajathu was described by almost all the Acharyas in their classical text books. Especially in Rasasastra text books, Shilajathu was included under Maharasa, Uparasa, Dhatu varga, Suvarnadi varga, Paradati varga. Description of different types of Shilajathu and their properties was seen in classics. Acharyas explained about the genuinity test of Shilajathu, various Sodhana procedures also mentioned for removing the impurities and make fit for consumption. Marana (incineration) and Satvapatana (extraction of essence) are not necessary for Shilajathu, whereas Guna (property), Karma (action), Matra (dose) of Shilajathu was available in literatures. For curing various diseases Shilajathu administered along with different Anupanas (adjuvant), it is considered as panacea. It is the one of the ingredients of various Ayurveda formulations and has Rasayana (rejuvenation) property. In this article, an attempt has made to summarize the wide range of description of Shilajathu available in various Ayurveda classics.